1995
DOI: 10.1242/jeb.198.12.2619
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of proton pumps (H+-ATPase) in pavement cells of rainbow trout gill

Abstract: The expression of the V-type proton ATPase (H+-ATPase) was examined in the gill of the freshwater rainbow trout (Oncorhynchus mykiss) using immunocytochemistry in concert with laser scanning confocal or electron microscopy. A synthetic peptide consisting of the carboxy-terminal region of the 31 kDa subunit of the bovine renal H+-ATPase was used to generate an antiserum in rabbits, and its suitability for use in trout gill was confirmed by western blotting. Gill epithelial cells demonstrated specific immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Since an apical V-H + -ATPase in freshwater teleost gills would directly pump protons into the environment, this transporter has also been hypothesized to play an important role in systemic acid-base balance. Experiments on rainbow trout have corroborated this hypothesis by demonstrating that gill V-H + -ATPase activity, immunoreactivity and mRNA expression all increase after exposure to environmental hypercapnia (Lin and Randall, 1993;Lin et al, 1994;Sullivan et al, 1995;Sullivan et al, 1996;Perry et al, 2000). Studies on branchial V-H + -ATPase in a true marine teleost have yet to be published, but the transporter's role in acid-base regulation of seawater teleosts is assumed to be minimal, given the favorable Na + gradient for Na + /H + exchangers (see Claiborne, 1998;Claiborne et al, 1999).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Since an apical V-H + -ATPase in freshwater teleost gills would directly pump protons into the environment, this transporter has also been hypothesized to play an important role in systemic acid-base balance. Experiments on rainbow trout have corroborated this hypothesis by demonstrating that gill V-H + -ATPase activity, immunoreactivity and mRNA expression all increase after exposure to environmental hypercapnia (Lin and Randall, 1993;Lin et al, 1994;Sullivan et al, 1995;Sullivan et al, 1996;Perry et al, 2000). Studies on branchial V-H + -ATPase in a true marine teleost have yet to be published, but the transporter's role in acid-base regulation of seawater teleosts is assumed to be minimal, given the favorable Na + gradient for Na + /H + exchangers (see Claiborne, 1998;Claiborne et al, 1999).…”
Section: Introductionmentioning
confidence: 84%
“…Recently, the V-H + -ATPase has also been considered important for driving Na + uptake across the gill epithelium of freshwater fishes. Similar to processes in frog skin, it was proposed that an apical V-H + -ATPase would generate a favorable electrical gradient to drive Na + uptake through an apical Na + channel (Lin and Randall, 1993;Lin et al, 1994;Sullivan et al, 1995). This model of ion uptake in freshwater teleosts was supported by the results of Wilson et al (Wilson et al, 2000), who found colocalization of the V-H + -ATPase with the epithelial Na + channel (ENaC) on the apical membrane of pavement cells from the leading edge of tilapia gills (Oreochromis mossambicus).…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Section 4.2.1, the activity of apical membrane H + ‐ATPase is thought to contribute to branchial Na + uptake by establishing a favourable electrical gradient for Na + uptake through conductive Na + channels such as ASICs (Figure 3, Table 1). However, independently of its linkage to Na + uptake, H + ‐ATPase activity may contribute directly to acid‐base regulation by facilitating H + secretion across the apical or basolateral membranes of select branchial ionocytes (Lin et al, 1994; Piermarini et al, 2002; Sullivan et al, 1995; Tresguerres et al, 2005; Wilson et al, 1997; Yan et al, 2007) (Figure 3). At the apical membrane, H + ‐ATPase enables outward H + excretion and thus facilitates net acid excretion.…”
Section: Mechanisms Of Acid‐base Regulationmentioning
confidence: 99%
“…Because it is powered by an active, ATP‐consuming transporter, unlike the NHE and NCC pathways of Na + uptake, the electrogenic model initially was touted as a more thermodynamically feasible model (Avella & Bornancin, 1989). H + ‐ATPase has since been localised in the gill epithelium of several species (Lin et al, 1994; Piermarini et al, 2002; Sullivan et al, 1995; Tresguerres et al, 2005; Wilson et al, 1997, 2000; Yan et al, 2007) and a role for H + ‐ATPase in Na + absorption has been demonstrated by Na + uptake inhibition in response to treatment with the H + ‐ATPase inhibitor bafilomycin under certain environmental conditions (Boisen et al, 2003; Fenwick et al, 1999; Grosell & Wood, 2002). Importantly, however, the expression of apical H + ‐ATPase, and its contribution to H + secretion and Na + uptake, is not ubiquitous across all fishes (Dymowska et al, 2012).…”
Section: Regulation Of Active Ion Uptake In Freshwatermentioning
confidence: 99%
“…Freshwater teleosts are faced with the challenge of diffusive ion loss to their hypo‐osmotic surroundings and thus actively take up Na + from the environment. The current dogma for freshwater fish gills proposes three Na + uptake mechanisms within ion transporting cells (ionocytes): (a) August Krogh's classic apical Na + /H + (NH4+) exchange, 1–3 (Figure 1A) mediated by Na + /H + exchangers (NHEs) and possibly augmented by outward transport of NH 3 by Rhesus (Rh) glycoproteins, 4–7 (b) uptake through, as of yet unidentified, apical Na + channel(s) (Figure 1B) or related acid‐sensing ion channel(s) (ASICs) 8,9 electrogenically coupled to apical H + excretion via V‐H + ‐ATPase (VHA), 10–12 and more recently (c) co‐transport of Na + and Cl − via Na + /Cl − Cotransporters (NCCs; Figure 1C). 13 These molecular mechanisms are analogous to apical Na + ‐reabsorption mechanisms in the mammalian kidney where roughly two‐thirds of Na + reabsorption occurs by proximal tubule NHEs and the remainder is mediated by NCCs and epithelial Na + channels (ENaCs) in the distal convoluted tubules and collecting ducts respectively 14–16 …”
Section: Introductionmentioning
confidence: 99%